(untitled) (Nordic Journal of African Studies, 2002)
The paper discusses three processes that make nasal consonants and especially /n/ the most dynamic area of Kitharaka (a Bantu language spoken in Kenya) phonology. Whereas the language has four underlying nasal segments, it has eleven consonants at the phonetic level.